2014
DOI: 10.1111/anu.12153
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the dietary substitution of fishmeal with tuna by-product meal on growth, body composition, plasma chemistry and amino acid profiles of juvenile Korean rockfish (Sebastes schlegeli)

Abstract: The effect of the substitution of fishmeal with tuna by-product meal (TBM) in the diet of Korean rockfish on growth, body composition, plasma chemistry and amino acid profiles was determined. Nine experimental diets were prepared. The control (Con) diet consisted of 550 g kg À1 fishmeal. The 10, 20, 30, 40, 60, 80 and 100 % fishmeal diets were substituted with tuna by-product meal (TBM), referred to as the TBM10, TBM20, TBM30, TBM40, TBM60, TBM80 and TBM100 diets, respectively. Finally, the fishmeal and soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
2
23
4
Order By: Relevance
“…In contrast to the results of this study, however, only 30 and 40% of fish meal could be replaced with TBM without a retardation in the growth of juvenile olive flounder (Kim et al ) and rockfish (Jeon et al in press), respectively. This difference could be explained by the fact that abalone is herbivorous (Thongrod et al ) and more effectively utilizes the soybean meal in TBM than do carnivorous fishes.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In contrast to the results of this study, however, only 30 and 40% of fish meal could be replaced with TBM without a retardation in the growth of juvenile olive flounder (Kim et al ) and rockfish (Jeon et al in press), respectively. This difference could be explained by the fact that abalone is herbivorous (Thongrod et al ) and more effectively utilizes the soybean meal in TBM than do carnivorous fishes.…”
Section: Discussioncontrasting
confidence: 96%
“…for 48 h and then dried. Our previous studies have revealed that up to 30 and 40% of fish meal could be replaced with TBM without a retardation in the growth of juvenile olive flounder, Paralichthys olivaceus , and rockfish, Sebastes schlegeli , respectively (Jeon et al in press; Kim et al ). Similarly, tuna muscle byproduct powder could replace 50% of fish meal protein without a reduction in growth performance of the olive flounder (Uyan et al ).…”
mentioning
confidence: 99%
“…The most important advantages of using fruit by‐products as abalone diet are to reduce the dependence of abalone on MA, which is expensive and limited in seasonal availability with low nutrition, and to eradicate cost of waste compilation, transportation and management programme. Similarly, some studies have been reported comparable growth performance of aquatic animals including abalone fed the diets substituting MA with food and plant by‐products (tuna by‐product, tunic meal of sea squirt, rice bran and white radish by‐product) for fish meal and MA (Choi et al, ; Jeon, Kim, Myung, & Cho, ; Lee et al, ; Lee, Kim, Choi, et al, ; Lee et al, ). The desirable effect of citrus peel on growth of land animals, such as rats (Lim, Lee, & Kim, ), broiler (Ebrahimi, Qotbi, Seidavi, & Bagar, ; Siyal et al, ) and rabbit (Ojabo, Adenkola, & Odaudu, ), has also been reported.…”
Section: Discussionmentioning
confidence: 88%
“…For example, white fish meal produced from byproducts contains 60%-67% crude protein, 7%-11% crude lipids, and 21%-23% ash, 18,34 and tuna fish meal produced from byproducts contains 57%-60% crude protein, 8%-14% fat, and 12%-21% ash. [35][36][37][38] The lower protein content and higher ash content in byproduct fish meals are not unexpected, as the nutrient composition differs between whole fish, fillets, and other parts of the body (viscera, heads, skin, bones, and blood). The different proportions of various byproducts that are used to produce fish meal will therefore also contribute to the nutrient variability of the fish meal made from byproducts.…”
Section: Fishery and Aquaculture Byproductsmentioning
confidence: 98%